2010
DOI: 10.1136/bmj.c1350
|View full text |Cite
|
Sign up to set email alerts
|

WHO guidelines for antimicrobial treatment in children admitted to hospital in an area of intense Plasmodium falciparum transmission: prospective study

Abstract: Objectives To assess the performance of WHO’s “Guidelines for care at the first-referral level in developing countries” in an area of intense malaria transmission and identify bacterial infections in children with and without malaria.Design Prospective study.Setting District hospital in Muheza, northeast Tanzania. Participants Children aged 2 months to 13 years admitted to hospital for febrile illness.Main outcome measures Sensitivity and specificity of WHO guidelines in diagnosing invasive bacterial disease; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
183
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(193 citation statements)
references
References 43 publications
7
183
3
Order By: Relevance
“…However, blood culture lacks sensitivity and early recognition and treatment of blood stream infections has the potential to avert progression to severe disease with high associated mortality [14,28]. While RDTs can improve targeting of anti-malarial drugs there is no comparable test for bacterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, blood culture lacks sensitivity and early recognition and treatment of blood stream infections has the potential to avert progression to severe disease with high associated mortality [14,28]. While RDTs can improve targeting of anti-malarial drugs there is no comparable test for bacterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is the most common bacterial coinfection in children with severe malaria [63][64][65]. Current WHO treatment guidelines suggest a low threshold for beginning antibiotic therapy in these children.…”
Section: Antibioticsmentioning
confidence: 99%
“…In 2010, Nadjm and others reported that the prevalence of invasive bacterial diseases was higher in malaria slide-negative patients and caused 17% of mortality. 1 The link between malaria and specific Gram-negative bacteria such as non-typhi Salmonella has, however, been reported in Africa. 1,2 In addition, it has been argued that the presence of malaria must not rule out the existence of other bloodstream infections, including bacteremias, in areas with high malaria prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…1 The link between malaria and specific Gram-negative bacteria such as non-typhi Salmonella has, however, been reported in Africa. 1,2 In addition, it has been argued that the presence of malaria must not rule out the existence of other bloodstream infections, including bacteremias, in areas with high malaria prevalence. 3 Thus, the WHO (World Health Organization) guidelines for the management of acute febrile illness in children recommend the use of an appropriate antibiotic in children exhibiting certain signs of severe illnesses.…”
Section: Introductionmentioning
confidence: 99%